Body build differentiation in athletes illustrated by multivariate methods - Pieatraszewska, J. (Human Movement, 2004)
Purpose. The so-called "master model" functioning in individual sports results from preliminary selection and specialist training. The objective of this paper is to assess the diversity of somatic build in young athletes of different track-and-field disciplines and describe the influence of special training on a young body.